2017
DOI: 10.1121/1.4979336
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neighborhood views containing multiple environmental features on road traffic noise perception at dwellings

Abstract: The importance of non-acoustical factors including the type of visual environment on human noise perception becomes increasingly recognized. In order to reveal the relationships between long-term noise annoyance and different types of neighborhood views, 2033 questionnaire responses were collected for studying the effect of perceptions of different combinations of views of sea, urban river, greenery, and/or noise barrier on the annoyance responses from residents living in high-rise apartments in Hong Kong. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Consistently, Van Renterghem and Botteldooren (2016) reported that the extent to which vegetation is visible through the living room window was a strong predictor of self-reported noise annoyance among residents with high exposure to traffic noise. Leung et al (2017) found that views of the sea, urban river, or greenery could reduce the probability of invoking a high noise annoyance response from residents living in high-rise buildings, while views of a noise barrier could increase the probability. Views of greenery had a stronger noise moderation capability than views of the sea or urban river.…”
Section: Auditory and Visual Interactionsmentioning
confidence: 99%
“…Consistently, Van Renterghem and Botteldooren (2016) reported that the extent to which vegetation is visible through the living room window was a strong predictor of self-reported noise annoyance among residents with high exposure to traffic noise. Leung et al (2017) found that views of the sea, urban river, or greenery could reduce the probability of invoking a high noise annoyance response from residents living in high-rise buildings, while views of a noise barrier could increase the probability. Views of greenery had a stronger noise moderation capability than views of the sea or urban river.…”
Section: Auditory and Visual Interactionsmentioning
confidence: 99%
“…More importantly, in-situ studies show similar positive effects of visible green. In two separate studies, one in Belgium 38 and one in Hong-Kong 32 , the sight of vegetation from within a dwelling decreased the level of self-reported noise annoyance by residents exposed to traffic noise.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on the effects of vegetation on sound appraisal range from research on the impact of landscapes and surroundings 31,32 , to the role of trees and vegetation on walls 13 , fences and (noise) barriers 33 . Traditionally, projections and images combined with headphones or speakers were used, whereas now integral technologies like virtual reality (VR) have become more common 16,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Van Renterghem & Botteldooren (2016) reported that the extent to which vegetation is visible through the living room window was a strong predictor of self-reported noise annoyance among residents with high exposure to traffic noise. Leung et al (2017) found that views of the sea, urban river, or greenery could reduce the probability of invoking a high noise annoyance response from residents living in high-rise buildings, while views of a noise barrier could increase the probability. Views of greenery had a stronger noise moderation capability than views of the sea or urban river.…”
Section: Introductionmentioning
confidence: 99%